Distribution characteristics of pandalid shrimps (Decapoda: Caridea: Pandalidae) along the Central Mediterranean Sea - FANELLI, E.; COLLOCA, F.; BELLUSCIO, A.; ARDIZZONE, G.D. (Mediterranean Marine Science, 2004)
The genus Plesionika is represented in the Mediterranean Sea by eight species, six of which,Plesionikaacanthonotus, P. antigai, P. edwardsii, P. gigliolii, P. heterocarpus and P. martia, are very common on muddy bottoms of the continental slope. During nine experimental trawl surveys a total of 29,038 individuals of these six pandalid species, was collected off the central western coasts of Italy (central Mediterranean) in order to study population structure and spatial distribution. P . antigaiinhabits the shelf break and upper slope; P. heterocarpus shows a wide bathymetric distribution, from the shelf-break to the upper slope; P. edwardsii and P. gigliolii occur in the upper slope. P. acanthonotus and P. martia occur in the deepest depths investigated. Segregation by size is revealed for the species that inhabit the same bottoms. The non-homogenous spatial distribution of Plesionikaspecies in the study area was probably related to the spatial differences in the magnitude of primary production in the area.